Suicide in Bangladesh: An Ecological Systems Analysis - S. M. Yasir Arafat; Tamkeen Saleem (Brain and Behavior)
ABSTRACT Background Suicide happens due to a complex interaction among multiple factors. Hence, prevention strategies should consider a wider range of personal and ecological aspects. It is an underprioritized public health problem in Bangladesh where risk factors for suicide have been poorly studied, and there is no national suicide prevention strategy. Therefore, exploring socioecological aspects of suicidal behavior would foster suicide prevention in the country. Objectives We aim to discuss the ecological model for suicide and suicide prevention in Bangladesh. Methods We performed a narrative review and organized the risk factors and prevention strategies according to the socioecological model in the context of Bangladesh. We used ecological systems to analyze risk factors for suicide and suicide prevention strategies in the country. Results Based on the available evidence, we categorized the risk factors for suicide into ontogenic system, microsystem, mesosystem, exosystem, macrosystem, and chronosystem. In addition, we contextualized the existing suicide prevention initiatives and potential suicide prevention strategies in ontogenic system, microsystem, mesosystem, exosystem, macrosystem, and chronosystem. Conclusions This article explored suicide and suicide prevention in Bangladesh through the lens of ecological systems theory that may foster the formulation of a national suicide prevention strategy in the country.